Theoretical Re-evaluations of Scaling Relations between SMBHs and Their Host Galaxies–2. Importance of AGN Feedback Suggested by Stellar Age–Velocity Dispersion Relation - Shirakata, Hikari; Kawaguchi, Toshihiro; Okamoto, Takashi; Ishiyama, Tomoaki (Frontiers in Astronomy and Space Sciences, 2017)
We present the galactic stellar age -- velocity dispersion relation obtained from a semi-analytic model of galaxy formation. We divide galaxies into two populations: galaxies which have over-massive/under-massive black holes (BHs) against the best-fitting BH mass -- velocity dispersion relation. We find that \textcolor{red}{galaxies with larger velocity dispersion have older stellar ages. We also find that} galaxies with over-massive BHs have older stellar ages. These results are consistent with observational results obtained from Martin-Navarro et al. (2016). \textcolor{red}{We tested the model with weak AGN feedback and find that galaxies with larger velocity dispersion have a younger stellar age.}